An exploration of enhancing thermal protective clothing performance by incorporating aerogel and phase change materials. (24th May 2017) - Zhang, Hui; Song, Guowen; Su, Hui; Ren, Haitao; Cao, Juan
Summary: Thermal liners play a critical role in thermal protective performance for firefighter gear. Effective engineering of textile material is necessary to enhance this protective performance. A modified thermal protective erformance (TPP) tester was used to study the influence of incorporating aerogel and microencapsulated phase change materials (MPCMs) in thermal liners (including a traditional thermal liner, phase‐change layer, and aerogel layer) and the relevant parameters associated with enhanced thermal liner performance. Two different phase‐transition temperature (45°C and 50°C) of MPCM were selected. The samples were exposed to a medium intensity radiation of 15 kW/m 2 for 240 seconds, and a skin burn model was applied for second‐degree burn prediction. Given the selected, results showed that the best TPP in this study was achieved when the phase‐transition temperature of MPCM was 45°C and the layering order consisted of the traditional thermal layer (closest to heat source), followed by an aerogel layer, and a final MPCM layer. The predicted second‐degree burn time was 218.3 seconds and increased by 90% compared with only containing traditional thermal liner with a thickness of 5 mm. For all 3 materials contained in the thermal liner, the relationship between absorbed energy and predicted second‐degree skin burn time indicated that they had a remarkable negative linear correlation ( R 2 was 0.9792). The experimental data and predicted results were in good agreement, with a correlation coefficient ( R 2 ) of 0.9911. The findings provide a scientific basis for future textile engineering and a novel approach to improve TPP.